Programa educativo de comunicación efectiva para el mejoramiento de la asertividad en directivos y docentes de la Institución Educativa Pública Secundaria Mariscal Oscar R. Benavides Iquitos 2024 - Huacachi Romero, Leonor (2025)
The objective was to evaluate the effect of the implementation of an effective communication educational program on improving assertiveness in managers of the "Mariscal Oscar R. Benavides" Secondary Public Educational Institution in Iquitos during 2024. An evaluative type of research was carried out, using longitudinal, field, quasi-experimental and univariate designs, with an experimental group and a control group. The population considered was 195 managers and teachers, the sample was 60, receiving a written performance test in the form of a pretest and post test, validated by experts. The results of the study indicated that the effective communication program had a significant effect. on increasing the assertiveness of managers and teachers during 2024. When comparing the levels of assertiveness in the Pretest and Posttest phases, the experimental group showed a significant increase in their score (from M = 9.05 to M = 12.20), with a p-value of .000 demonstrating a statistically relevant improvement. In contrast, the control group did not show any relevant changes in their levels of assertiveness. These findings emphasize the effectiveness of the implemented program and highlight the importance of communication training to strengthen interpersonal skills in the educational context.